Supporting Subject Justification by Educational Psychology: A Systematic Review of Achievement Goal Motivation in School Physical Education - Jaitner, David; Rinas, Raven; Becker, Christoph; Niermann, Christina; Breithecker, Jennifer; Mess, Filip (Frontiers in Education, 2019)
Achievement Goal Theory (AGT) has been applied as core concept for understanding and promoting students’ motivation in physical education (PE) and shows considerable relevance for theoretically and empirically justifying the significance of PE. However, systematically organized reviews of empirical research on AGT are limited to physical activities without explicit PE perspective. First, we aimed to compile basic tenets of AGT and its pedagogical potential for PE. Second, to bring together key findings and discuss future research, we systematically examined the existing empirical literature that applied AGT constructs in both observational and interventional PE settings. We searched the Web of Science, Scopus, Education Source, ERIC, SPORTDiscus, Physical Education Index, PsychInfo, and PsychArticles databases to identify English-language peer-reviewed journal articles with no restriction to publication date. The review was conducted according to the PRISMA Statement. Two independent reviewers screened all studies identified for eligibility, and assessed the methodological quality as well as the risk of bias. A total of 91 studies were included for analysis. Most of the studies (70) were observational, 21 studies were intervention based. On average, the methodological quality of the included studies was moderate and the risk of bias was moderate to high. Mastery goals, mastery-approach goals, and mastery climates appear to be highly relevant for supporting multiple political and curricular PE aims such as psychological well-being, motor skill development, general sports participation, prosocial behavior, and aspects of healthy living. Achievement goal profiles combining high mastery goals, high to low performance goals, and performance-approach goals partly show desirable functions. The results provide comprehensive information for planning and shaping PE lessons based on AGT constructs that match the intended ambitions. The integration of the results into everyday school PE practice is a promising avenue for promoting students’ motivation in PE and for fulfilling the overall political and curricular aims. However, this may be challenging in PE practice, as PE teachers at least partially follow a performance-pedagogical structure, including an orientation towards agonal sports, competition, and social comparison.